K-edge structure in shock-compressed chlorinated parylene - Bailie, D; White, S; Irwin, R; Hyland, C; Warwick, R; Kettle, B; Breslin, N; Bland, SN; Chapman, DJ; Mangles, SPD; Baggot, RA; Tubman, ER; et al. (MDPI, 2023)
We have carried out a series of experiments to measure the Cl K-absorption edge for shock-compressed samples of chlorinated parylene. Colliding shocks allowed us to compress samples up to four times the initial density with temperatures up to 10 eV. Red shifts in the edge of about 10 eV have been measured. We have compared the measured shifts to analytical modelling using the Stewart–Pyatt model and adaptions of it, combined with estimates of density and temperature based on hydrodynamic modelling. Modelling of the edge position using density functional theory molecular dynamics (DFT-MD) was also used and it was found that good agreement was only achieved when the DFT simulations assumed conditions of lower temperature and slightly higher density than indicated by hydrodynamic simulations using a tabular equation of state.